Development of sustainable biomass residues for biofuels applications - Shah M.A.; Hayder G.; Kumar R.; Kumar V.; Ahamad T.; Kalam M.A.; Soudagar M.E.M.; Mohamed Shamshuddin S.Z.; Mubarak N.M. (Nature Research, 2024)
A comprehensive understanding of physiochemical properties, thermal degradation behavior and chemical composition is significant for biomass residues before their thermochemical conversion for energy production. In this investigation, teff straw (TS), coffee husk (CH), corn cob (CC), and sweet sorghum stalk (SSS) residues were characterized to assess their potential applications as value-added bioenergy and chemical products. The thermal degradation behavior of CC, CH, TS and SSS samples is calculated using four different heating rates. The activation energy values ranged from 81.919 to 262.238 and 85.737212.349 kJmol?1 and were generated by the KAS and FWO models and aided in understanding the biomass conversion process into bio-products. The cellulose, hemicellulose, and lignin contents of CC, CH, TS, and SSS were found to be in the ranges of 31.5641.15%, 23.932.02%, and 19.8525.07%, respectively. The calorific values of the residues ranged from 17.3 to 19.7MJ/kg, comparable to crude biomass. Scanning electron micrographs revealed agglomerated, irregular, and rough textures, with parallel lines providing nutrient and water transport pathways in all biomass samples. Energy Dispersive X-ray spectra and X-ray diffraction analysis indicated the presence of high carbonaceous material and crystalline nature. FTIR analysis identified prominent band peaks at specific wave numbers. Based on these findings, it can be concluded that these residues hold potential as energy sources for various applications, such as the textile, plastics, paints, automobile, and food additive industries. 2023, Springer Nature Limited.